Academic mobility - Maadad, Nina; Tight, Malcolm (International perspectives on higher education research ;, 2014)
This book offers a contemporary perspective on the mobility of academics across the globe. With contributions from authors based across 4 continents focusing on the experience of academic mobility in Africa, Australia, Europe, the Gulf and the United States, the volume is both comprehensive and relevant.